Food system under COVID-19 lockdown in Shanghai: problems and countermeasures - Han, Shuyu; Jia, Lei; Liu, Zengjin; Fuyuki, Katsuhito; Imoto, Tomoko; Zhao, Xintong (Frontiers in Sustainable Food Systems, 2024)
Owing to the increased transmissibility of the Omicron virus, Shanghai implemented a citywide lockdown in 2022. This measure disrupted the normal functioning of the city's food system and led to incidents related to food insecurity within the city. To mitigate these challenges, the local government and various stakeholders devised various solutions. In this context, we adopted a root cause analysis to report the disruptions caused by the lockdown on Shanghai's food system, examined the underlying reasons behind food system incidents, and discussed the solutions implemented by the government and stakeholders. Additionally, we assessed the contributions of these solutions in promoting urban food system resilience during lockdown. Finally, we scrutinized the sustainability of the solutions implemented in Shanghai. The findings of this research is anticipated to provide valuable insights for other areas that may encounter similar challenges in the future while fortify their urban food systems.